(3EcSjQ GdJjSjQ deMahXGJ LeY GdJcSjQs - (3eNaV Hf eMeO Hf GdGejf Hf MhHc GdJehfdcjs
(3ChdgG (B:s
(3CeG HYO , agPG JYdja Ydi eG fXeI TjNfG aMV HGH ef eMahXGJ LeY GdJcSjQ Ke HYO JeGe GdcdGe Ydi eMahXGJ CLdH fU GdcGajI hGdJSgjd ajg aLGA gPG GdJYdjb s
(3BNQgG (B:s
(3JfbU ef BNQgG , BNQ GdehLhO (B: (3hfU GdcGajI ajg (B: (3hai aYjd hbYjGf fbd EPG GSJHGf HgeG eYfi aYd hfU GdJSjgd ajg hdeG GfJgi GdcdGe Ydi eMahXGJ aYGFd GfJbd jJcde s
(3HgG fXGe GdJYbjHIs
(3fSNI bOjeIs
(3HYV YHGQGJgG HGdMeQI s
(3eJbUaI GdCWQGa s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdUQas